2017
DOI: 10.1073/pnas.1707662114
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation on O-glycans protects platelets from clearance by liver Kupffer cells

Abstract: Most platelet membrane proteins are modified by mucin-type core 1-derived glycans (O-glycans). However, the biological importance of O-glycans in platelet clearance is unclear. Here, we generated mice with a hematopoietic cell-specific loss of O-glycans (HC ). These mice lack O-glycans on platelets and exhibit reduced peripheral platelet numbers. Platelets from HC mice show reduced levels of α-2,3-linked sialic acids and increased accumulation in the liver relative to wild-type platelets. The preferential accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 42 publications
6
94
2
Order By: Relevance
“…As well, it was recently shown that desialylated epitopes on GPIba do not significantly bind the AMR. 75 This evidence supports the idea of an AMR-independent pathway in GPIba-mediated hepatic TPO generation. This may be also the reason why Aspgr1 2/2 (AMRdeficient) mice do not exhibit a significant decrease in plasma TPO.…”
Section: Discussionsupporting
confidence: 79%
“…As well, it was recently shown that desialylated epitopes on GPIba do not significantly bind the AMR. 75 This evidence supports the idea of an AMR-independent pathway in GPIba-mediated hepatic TPO generation. This may be also the reason why Aspgr1 2/2 (AMRdeficient) mice do not exhibit a significant decrease in plasma TPO.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, a publication reported that desialylation leads to removal of transfused platelets by a two-step mechanism in which platelets adhere to and then roll on hepatocyte microvilli by interacting with the AMR, followed by their capture through the CLEC4F receptor on Kupffer cells (Li et al, 2017). In our study, using state-of-the-art SD-IVM with high spatiotemporal resolution, we did not observe deceleration or rolling of platelets on hepatocytes but rather direct capture by Kupffer cells.…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore, it is likely that GPIbα desialylation contributes to platelet clearance by enhancing platelet activation and PS-dependent platelet phagocytosis. In support of this, platelets lacking sialylation of O-glycans were also primarily phagocytosed by macrophages in the liver (62). This explanation might also apply to GPIbα desialylation-mediated chilled platelet clearance (43,63).…”
Section: Discussionmentioning
confidence: 75%